Co2+-dependent gene expression in Streptococcus pneumoniae: opposite effect of Mn2+ and Co2+ on the expression of the virulence genes psaBCA, pcpA, and prtA - Manzoor, Irfan; Shafeeq, Sulman; Kloosterman, Tomas G.; Kuipers, Oscar P. (Frontiers in Microbiology, 2015)
Manganese (Mn2+)-, zinc (Zn2+)- and copper (Cu2+) play significant roles in transcriptional gene regulation, physiology and virulence of Streptococcus pneumoniae. So far, the effect of the important transition metal ion cobalt (Co2+) on gene expression of S. pneumoniae has not yet been explored. Here, we study the impact of Co2+ stress on the transcriptome of S. pneumoniae strain D39. BLAST searches revealed that the genome of S. pneumoniae encodes a putative Co2+-transport operon (cbi operon), the expression of which we show here to be induced by a high Co2+ concentration. Furthermore, we found that Co2+, as has been shown previously for Zn2+, can cause derepression of the genes of the PsaR virulence regulon, encoding the Mn2+-uptake system PsaBCA, the choline binding protein PcpA and the cell-wall associated serine protease PrtA. Interestingly, although Mn2+ represses expression of the PsaR regulon and Co2+ leads to derepression, both metal ions stimulate interaction of PsaR with its target promoters. These data will be discussed in the light of previous studies on similar metal-responsive transcriptional regulators.